ANALISIS DISTRIBUSI PENDAPATAN PADA USAHA IKAN NILA DI KECAMATAN SEGINIM, KABUPATEN BENGKULU SELATAN - Sriyoto, Sriyoto; Reswita, Reswita; Hardianto, Hardianto (Jurnal AGRISEP, 2015)
Indonesia has a very rich fisheries resources and potential both in the fresh waters, the coast, and sea water covering land diversity of fish and fisheries. One type of fresh water fish that has been cultivated is Tilapia. In Indonesia, Tilapia is economically valuable fish which has been cultivated by fish farmers in various areas. Seginim district in Southern Bengkulu is one region in Sumatera that produces cultivator of Tilapia. The objectives of this study were to 1) know the income of Tilapia farmers and 2) know the income distribution in the business of Tilapia. The determination of respondents in this research was taken from the business of Tilapia. The respondents were determined by using census method and the number of respondents were 54 people. The primary data was taken directly from the respondents by using interview method to the enterpreneuss, and by using questionaires. The secondary data was obtain from the Seginim district office and related literature.the analysis instrument used was the income analysis and income distribution of the business of Tilapia. The results of the study showed that the income of the business of Tilapia in Seginim district of Southern Bengkulu was Rp22,204,786.27 per farm per season. The part obtained by fish feed businessman was 45.17 percent; by fish seed businessman was 29.25 percent; by fish farmers was 19.22 percent; and by farm workers was 6.36 percent.